Eosinophilic Perimyositis In a Young Male: A Case Report and Review of Literature - Bimal Patel (GAIMS Journal of Medical Sciences)
Eosinophilic myositis is rare group of disorder characterized by eosinophilic infiltration of skeletal muscles. It generally presents with pain, swelling and weakness of the affected muscle group or limb. The main cause of skeletal muscle eosinophil infiltration is parasitic infections. Other conditions such as hypereosinophilic syndrome, muscle dystrophies, drugs or toxins can also cause such a condition. However, most cases have no known etiological factor and are considered as idiopathic. Idiopathic eosinophilic myositis can be classified into three subtypes: focal eosinophilic myositis, eosinophilic polymyositis, and eosinophilic perimyositis which can be differentiated by pathological studies. The present report is a case of eosinophilic perimyositis who presented with pain and swelling in the region of right thigh.